Oesofagogastroduodenal endoscopic features in patientswith cirrhotic partal hypertension - M. Enver DOLAR; Mahmut ÖZTÜRK; Macit GÜLTEN; S. Giray NAK; Faruk MEMİK (Turkish Journal of Gastroenterology, 2020)
-